Matrix operators on the new spaces of λ-difference sequences - Al-Sabri, Omar H.; K. Noman, Abdullah (IJRDO -JOURNAL OF MATHEMATICS, 2022)
In the present paper, we have concluded the α-, β- and γ-duals of the λ-difference spaces c0(∆λ); c(∆λ) and ℓ1(∆λ) which have recently been introduced. Further, we have characterized the matrix operators acting on, into and between these new sequence spaces.